Enhancement of wheat resistance to dry–hot wind stress during grain filling by 24-epibrassinolide: optimization of hormone balance and improvement of flag leaf photosynthetic performance - Wang, Chao; Cui, Haixing; Jin, Min; Wang, Jiayu; Li, Chunhui; Li, Yong; Luo, YongLi; Wang, Zhenlin (Frontiers in Plant Science, 2025)
IntroductionDry-hot wind during the grain filling period is a prevalent agrometeorological challenge worldwide, causing significant functional leaf senescence, disrupting the grain filling process, and ultimately leading to wheat yield loss. Although studies have explored the alleviating effects of EBR under abiotic stress, its application in wheat and the potential mechanisms underlying its role in mitigating dry–hot wind still require further investigation.MethodsUsing the dry–hot-wind-sensitive cultivar Jinan 17 (JN17) and the dry–hot-wind-resistant cultivar Liangxing 77 (LX77) as experimental materials. A split-plot design was employed, with cultivar as the main plot factor, dry-hot wind (DH) treatment as the subplot factor, and the foliar application of 24-epibrassinolide (EBR) at a concentration of 0.1 mg L-1 as the sub-subplot factor.ResultsEBR alleviated the negative effects of DH stress on wheat by optimizing the hormone balance. The abscisic acid (ABA) and jasmonic acid (JA) contents decreased, and the salicylic acid (SA) content increased, which promoted the stomatal opening of flag leaves. The transpiration rate (Tr) was increased by 7–10% and thus reduced the temperature of the spikes and leaves by 0.87–1.27 °C and 1.6–2.4 °C, respectively. Additionally, the activities of antioxidant enzymes, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), were enhanced, which prevented early flag leaf senescence and maintained a high chlorophyll level under DH stress. Therefore, the photosynthetic performance of flag leaves was enhanced. EBR enhanced the yield of JN17 and LX77 under DH stress. JN17’s yield was increased by 9.2% and 7.5% in the 2020–2021 and 2021–2022 wheat growing seasons, respectively, and LX77’s yield was increased by 4.9% and 2.3% over two years.DiscussionThis study provides a promising approach for enhancing wheat’s resistance to DH stress, with practical implications for wheat production.